(untitled) (SCIENCE TIME JOURNAL, 2026)
The article examines the main principles and methodological approaches to teaching English in the context of inclusive education. It analyzes the characteristics of perception and acquisition of a foreign language by students with special educational needs (SEN), including learners with hearing and visual impairments, musculoskeletal disorders, autism spectrum disorders, attention deficit hyperactivity disorder, and specific learning difficulties such as dyslexia. The paper substantiates the necessity of adapting instructional materials, didactic tasks, and assessment methods. Particular attention is paid to the role of the English teacher in creating a psychologically safe educational environment that ensures equal access to communication and language development. The article concludes with practical recommendations for organizing an inclusive English lesson.